Association between resting amygdalar activity and abnormal cardiac function in women and men: a retrospective cohort study. (9th April 2019) - Fiechter, Michael; Roggo, Andrea; Burger, Irene A; Bengs, Susan; Treyer, Valerie; Becker, Anton; Marȩdziak, Monika; Haider, Ahmed; Portmann, Angela; Messerli, Michael; Patriki, Dimitri; Mühlematter, Urs J; et al.
Abstract: Aims: Cardiovascular outcomes of women with coronary artery disease (CAD) are perceived as relatively worse when compared to men. Amygdalar metabolic activity has recently been shown to independently predict cardiovascular events in patients without known cardiovascular disease. Given that traditional algorithms for risk prediction perform worse in women than in men, we sought to assess sex-specific associations between amygdalar metabolic activity and cardiac dysfunction with suspected or known CAD. Methods and results: This retrospective study included 302 patients (mean age 66.8 ± 10.2 years, 29.1% women) selected for evaluation of CAD, malignant, or inflammatory disease. All patients had undergone both, myocardial perfusion imaging by single photon emission computed tomography (MPI-SPECT) and whole-body fluoro-18-deoxyglucose ( 18 F-FDG) positron emission tomography (PET), within 6 months. 18 F-FDG resting amygdalar uptake was significantly increased in women with abnormal MPI scans (standardized uptake value 33.4 ± 6.5 vs. 30.4 ± 4.7, P  = 0.043), while no such difference was observed in men ( P  = 0.808). In women, but not in men, a negative association between 18 F-FDG resting amygdalar activity and left ventricular ejection fraction (LVEF) was observed (Pearson r = −0.308, P  = 0.004). Accordingly, either LVEF [B-coefficient (standard error, SE) = −0.232 (0.109), P  = 0.045] or abnormal MPI [B-coefficient (SE) = 8.264 (2.449), P  = 0.003] were selected as significant predictors of high amygdalar 18 F-FDG uptake in a fully adjusted linear regression model in women, and a first order interaction term consisting of sex and LVEF or sex and abnormal MPI was significant ( P  = 0.035 and P  = 0.001, respectively). Conclusion: Resting amygdalar metabolic activity is associated with abnormal cardiac function and perfusion in women, suggesting a link between emotional stress and cardiovascular disease in women.